Marketing relacji w działalności innowacyjnej przedsiębiorstw na rynku Unii Europejskiej - Dolińska, Małgorzata (Relationship Marketing in an Enterprise Activity on the EU Market, 2006)
Network organization activity in accordance with relationship marketing conception in innovation processes becomes of strategic importance for global economy development. Innovation process consist of the following activities: search of innovation conception, solution elaboration, innovation application in an enterprise, promotion and sale of it in the market, and also continuous development of il al the time. Enterprises, research and development, financial support and innovation transfer institutions as partners of regional innovation system collaborate among themselves in innovation processes in accordance with relationship marketing conception and within the limits of network organization. The purpose of firm collaboration with its clients and partners in innovation process is the improvement of its competitive position in the market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 249-257